High incidence of metachronous advanced adenoma and cancer after endoscopic resection of colon polyps ≥20 mm in size. Issue 2 (16th November 2015) - Yoshida, Naohisa; Naito, Yuji; Siah, Kewin Tien Ho; Murakami, Takaaki; Ogiso, Kiyoshi; Hirose, Ryohei; Inada, Yutaka; Inoue, Ken; Konishi, Hideyuki; Kugai, Munehiro; Morimoto, Yasutaka; Hasegawa, Daisuke; et al.
Abstract : Background and Aim: There are limited studies on incidence rates of metachronous neoplastic lesions after resecting large colorectal polyps. In the present study, we analyzed metachronous lesions after endoscopic resection of colorectal polyps ≥20 mm in size. Methods: We retrospectively analyzed consecutive patients who underwent endoscopic resection of polyps from 2006 to 2013 at two affiliated hospitals. All patients underwent at least two total colonoscopies before follow up to ensure minimal missed polyps. Only patients who had follow‐up colonoscopy annually after resection were recruited. We separated patients according to size of polyp resected; there were 239 patients in the ≥20‐mm group and 330 patients in the <20‐mm group. Clinical characteristics and cumulative rates of metachronous advanced adenoma and cancer in both groups were analyzed. Advanced adenoma was defined as a neoplastic lesion ≥10 mm in size and adenoma with a villous component. Results: Cumulative rate of development of metachronous advanced adenoma and cancer in the ≥20‐mm group was significantly higher than in the <20‐mm group (22.9% vs 9.5%, P < 0.001) at 36 months. There was also more development of small polyps 5–9 mm in the ≥20‐mm group than in the <20‐mm group (45.2% vs 28.8%, P < 0.001). With respect to metachronous lesions, there were more right‐sided colonic lesions in the ≥20‐mm group than in the <20‐mm group (78.8% vs 50.0%, P = 0.015). Conclusion: High incidence rates of development of metachronous neoplastic lesions were detected after resection of colorectal polyps ≥20 mm in size.